IDENTIFIKASI JENIS BATUAN MENGGUNAKAN METODA GEOLISTRIK TAHANAN JENIS KONFIGURASI WENNER DI UNIVERSITAS NEGERI PADANG KAMPUS AIR TAWAR - Elvi Novia S (PILLAR OF PHYSICS, 2013)
The research about kinds of rocks has been done in Padang State University Air Tawar campus. Kinds of rocks can be determined by knowing the resistivity value. Wenner resistivity geoelectrical method was used to determine the rocks resistivity value. The research was done to determine the rocks resistivity value and kinds of rocks in Padang State University, Air Tawar campus. Automatic measurement was done using ARES (Automatic Resistivity) and interpretation of data was done using Res2dinv software and Least Square inversion. The result of data interpretation shows range of rocks resistivity value at sounding point 00053’44,0”S and 100020’79,8”E in 1st line is 0,675 – 300,1 Ωm, at sounding point 00053’53,1”S and 100021’02,8”E in 2nd line is 0,0145 – 208 Ωm, at sounding point 00053’48,9”S dan 100020’50,6”E in 3rd line is 0,118 – 243,7 Ωm, and at sounding point 00053’55,7”S and 100021’02,3”E in 4th line is 0,195 - 1842 Ωm. Kinds of rocks that are found in the research are Clays, Sandstones, Alluvium, Sands and also Groundwater.   Keywords: Resistivity geoelectrical, Wenner configuration, Rock